(untitled) (Intent Research Scientific Journal, 2023)
Cotton’s demand for water depends on many factors in its development at different stages. In this article, cotton and grain planting techniques and economic conditions are studied. In specific climate and soil- ameliorative conditions, scientifically based irrigation norms are of great importance for increasing cotton productivity with economic ( economical ) use of water . In this case, it is necessary to take into account the years of low water and severe shortage of irrigation water.